Antioxidant Activity of Hotong (Setaria italica) Seeds from Buru and its Implications for Biochemistry Learning - Awan, Ali; Kurnia, Tri Santi; Pattiasina, Eifan Boyke (KnE Social Sciences, 2024)
Hotong Buru seeds (Setaria italica) are a local wisdom food ingredient in South Buru Regency, Maluku Province, Indonesia. These hotong seeds are widely consumed by the people of South Buru as a staple food substitute for rice. Hotong Buru seeds contain bioactive components that have antioxidant properties, including tannins and Vitamin E. Tannins are polyphenols, one of the anti-nutrients found in food ingredients. These components are mostly contained in the epidermis. This research aims to analyze the antioxidant activity of Hotong Buru (Setaria italica) seeds and their implication for Biochemistry Learning. Antioxidant analysis was conducted using 1,1-dephenyl-2-picryl-hydrazyl (DPPH) as a free radical. Descriptive analysis was used to describe the chemical composition and quality of Hotong Buru seeds in tables and graphs. Inferential analysis was done using one way ANOVA technique to analyze the effect of food quality. All data were presented descriptively, and antioxidant activity was calculated using the SPSS Program. The results showed that Hotong seeds from Buru Island positively contain secondary metabolite compounds such as alkaloids, flavonoids, terpenoids, steroids, tannins, and saponins. The content of these secondary metabolites can act as antioxidants for the human body. Antioxidants are very important to delay or inhibit damage to molecular compounds. In addition, the results of this study are implicated in biology learning, especially biochemistry, food science, and nutrition courses. The phytochemical test showed that there were antioxidants in Hotong Buru seeds ingredients, there are alkaloids, flavonoids, steroids, tannins, terpenoids, and saponins. The implications of research results for biology learning have been made clear in the form of practical instructions that have been applied to students of the Pattimura University Biology Education Study Program. Keywords: Hotong buru, antioxidants, culinary ingredients, biochemistry learning